2004
DOI: 10.1002/chem.200305123
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fluorescence of Remote Functionalized Diaminodicyanoquinodimethanes in the Solid State and Fluorescence Switching in a Doped Polymer by Solvent Vapors

Abstract: Remote functionalized zwitterionic diaminodicyanoquinodimethanes are found to exhibit a dramatic enhancement of light emission in the solid state and when doped in polymer films, as compared to the solution state. Crystal structure analysis of prototypical molecules reveals the role of the remote functionality in the solid state molecular organization. Semiempirical quantum chemical computations provide a viable model to explain the interesting phenomenon of fluorescence enhancement as arising from the inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 27 publications
6
107
0
Order By: Relevance
“…[17] Crystal structure analysis showed that BDPDQI possesses a centrosymmetric lattice belonging to the monoclinic P2 1 /c space group with one molecule in the asymmetric unit. The molecular structure is shown in Figure 1 (left), and the crystallographic details are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[17] Crystal structure analysis showed that BDPDQI possesses a centrosymmetric lattice belonging to the monoclinic P2 1 /c space group with one molecule in the asymmetric unit. The molecular structure is shown in Figure 1 (left), and the crystallographic details are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…[17] We have now observed spontaneous resolution through helical organization in crystals of a related molecule decorated with a variety of ionic and potential hydrogen bonding sites. 7-(N,N-dimethylpiperazinium)-7-oxo-8,8-dicyanoquinodimethane (DPODQ) (Scheme 1) possesses cyano groups, an amide group, and a quarternary ammonium functionality capable of participating in hydrogen bonds (O À H¥¥¥N and C À H¥¥¥O) or electrostatic interactions.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…If this is the case, aggregation (solidification) should lead to a reduction in the probability and amplitude of molecular motions such as twisting and out-of-plane bending motion, which might trigger radiationless transitions, thereby enhancing the fluorescence efficiency as a whole. Such an aggregation-induced enhanced emission [35][36][37][38][39][40][41][42][43] was also found during the measurements of the photophysical properties of arylethene-based -systems in dioxane/water mixtures. The following example of 14e is typical (Fig.…”
Section: Rapid and Systematic Construction Of Triarylethene-based Extmentioning
confidence: 75%
“…26). 18,[35][36][37][38][39][40][41][42][43] For example, as well as highly fluorescent 14, otherwise nonfluorescent -systems such as 15 and 16 also became fluorescent in the solid state. The max values of the solid-state emission were found to be similar to those obtained in chloroform solution.…”
Section: Rapid and Systematic Construction Of Triarylethene-based Extmentioning
confidence: 99%